2023
DOI: 10.3847/1538-4357/acc401
|View full text |Cite
|
Sign up to set email alerts
|

HOPS 361-C’s Jet Decelerating and Precessing through NGC 2071 IR

Abstract: We present a two-epoch Hubble Space Telescope study of NGC 2071 IR highlighting HOPS 361-C, a protostar producing an arced 0.2 parsec-scale jet. The proper motions for the brightest knots decrease from 350 to 100 km s−1 with increasing distance from the source. The [Fe ii] and Paβ emission line intensity ratio gives a velocity jump through each knot of 40–50 km s−1. A new [O i] 63 μm spectrum, taken with the German REciever for Astronomy at Terahertz frequencies instrument aboard Stratospheric Observatory for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 118 publications
0
2
0
Order By: Relevance
“…(1) on the smallest scales and shocks in outflows at larger distances from protostars (e.g., Komarova & Fischer 2020;Rubinstein et al 2023b), while the [Fe II] and H 2 lines trace shocks in outflows (e.g., Stapelfeldt et al 1991;Zinnecker et al 1998;Reipurth et al 2000). The CO emission is known to arise from both inner disks and outflows (e.g., Herczeg et al 2011;Salyk et al 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) on the smallest scales and shocks in outflows at larger distances from protostars (e.g., Komarova & Fischer 2020;Rubinstein et al 2023b), while the [Fe II] and H 2 lines trace shocks in outflows (e.g., Stapelfeldt et al 1991;Zinnecker et al 1998;Reipurth et al 2000). The CO emission is known to arise from both inner disks and outflows (e.g., Herczeg et al 2011;Salyk et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…along jets are few. Although atomic hydrogen has been observed in jets in the form of HH objects (e.g., Lizano et al 1988;Garcia Lopez et al 2008Smith et al 2010;Reiter et al 2015;Rubinstein et al 2023b), in only a few instances has Brγ emission been found along a jet (Beck et al 2010) or in a jet knot (Davis et al 2011). To our knowledge, our data show the first collimated protostellar jets detected in the Brα line.…”
Section: Collimated Bipolar Jetsmentioning
confidence: 99%